The Effect of Song Towards Students’ Mastery on Simple Past Tense - Mira Yeni; Citra Ayu; Vitri Angraini Hardi (Journal of English Language and Education, 2021)
The research was conducted because of students face difficult to remember Simple Past Tense formula. The experimental research was conducted at the tenth grade at SMAN 01 Bangkinang kota. This research aims to know the effect of song towards Students’ Matery on Simple Past. The research methodology uses a Quasi-experimental design. The sample of this research was class X MIPA 4 as the experimental class and X IPS 2 as the control class. The experimental class consisted of 33 students and the control class consisted of 36 students. This research uses cluster random sampling which selects classes randomly from MIPA and IPS Class. The instrument used in this research was a test. Data analysis used SPSS 25 test of Hypotesis. Based on the results of the study, the average score of students in the experimental class was 71.97 and 55.69 in the control class. Data analysis showed a significance of 0.000 > 0.05, it means that Ha is accepted. The key is that there is an effect of Song towards Students’ Mastery on Simple Past Tense.